Tropospheric ozone from space: tracking pollution with the TOMS (Total Ozone Mapping Spectrometer) instrument - Thompson, Anne M.; Hudson, R.D.; Frolov, A.D.; Witte, J.C.; Kucsera, T.L. (IEEE, 2001)
Two new products have been developed from the TOMS (Total Ozone Mapping Spectrometer) satellite instrument to resolve pollution in the tropics and mid-latitudes. The modified-residual technique uses v.7 TOMS total ozone and is applicable to tropical regimes in which the wave-one pattern in total ozone is observed. The second method, the TOMS-direct method is a new algorithm that uses TOMS radiances to extract tropospheric ozone in regions of constant stratospheric ozone. In these regions, tropospheric ozone displays the high mixing ratios seen in urban pollution episodes. Electronic versions of daily and 9-day averaged modified-residual tropospheric ozone ("TTO" data and images) for the Nimbus 7/TOMS observing period (1979-1992) and the Earth Probe/TOMS (8/1996-2000) are available at 1-degree latitude /spl times/ 1.25-degree longitude resolution at http://metosrv2.umd.edu//spl sim/tropo. The 1998-2000 TTO (tropical tropospheric ozone) column amounts have been validated using data from a network of ozonesonde stations; http://code916.gsfc.nasa.gov/Data_services/shadoz.
IEEE International Symposium on Geoscience and Remote Sensing (IGARSS), Sydney, NSW, Australia, 09-13 July 2001
Keywords: Aerosols; Instruments; Fires; Satellites; Spectroscopy; North America; Oceans; Pollution; NASA; Continents